Climate Regulation and Emissions Abatement: Theory and Evidence from Firms’ Disclosures - Ramadorai, Tarun; Zeni, Federica (Management Science, 2024)
We measure firms’ beliefs about climate regulation, plans for future abatement, and current emissions mitigation from responses to the Carbon Disclosure Project. These measures vary strikingly around the Paris announcement. A dynamic model of a representative firm facing a future carbon levy, trading off abatement and capital growth, and facing convex adjustment costs cannot fit the data. A two-firm model with crossfirm reputational externalities, heterogeneous beliefs over climate regulation, and leader-follower interactions does. Out of sample, the model predicts firms’ reactions when the United States exits the Paris agreement. Firms’ beliefs about climate regulation strongly affect abatement, and crossfirm interactions amplify regulatory impacts. This paper was accepted by Victoria Ivashina, finance. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2021.00482 .